KEARIFAN LOKAL ADAT ‘TUTUP BAILEO’ DI DESA ALLANG KECAMATAN LEIHITU BARAT KABUPATEN MALUKU TENGAH - Patty, William G.; Zakarias, Jhon D.; Paat, Cornelius (HOLISTIK, Journal Of Social and Culture, 2021)
Local wisdom is part of a society's culture that cannot be separated from the language of the community itself. Local wisdom is usually passed down through generations through word of mouth. Local wisdom itself contains very important knowledge about cultured life so that local wisdom is used as an asset of the nation's culture.Maluku is an archipelago province in eastern Indonesia that has cultural diversity from various sub-ethnic. Diversity is meant to show self-identity, various identity of one of them is traditional house. Various forms of construction and building materials have meaning according to the perspective of various sub-ethnic.Traditional houses are used for a variety of traditional and kinship activities, ranging from the life cycle from birth to adulthood to marriage even to death. Baileo is a physical building, but in Baileo there is actually a social space that gathers all the public interest so that historical and cultural facts have different meanings in each indigenous environment, including indigenous peoples in The Land of Allang. In Allang State, the clans Siwalette and Sabandar can only occupy the social layout of Baileo. On that basis, Baileo remained sanctity, seen as sacred in the practice of indigenous life. This kind of living system is only possible in community groups whose principle of life is guided by cultural references.Keywords: Local wisdom, traditional house, culture